Evaluation of anthelmintic activity of Trichosanthes dioica (r.) - NITIN KUMAR,; ANURAG, (International Journal of Pharma and Bio Sciences, 2016)
Trichosanthes dioica seeds are mentioned in various traditional texts as a drug used for vermicidal anthelmintic, insecticidal, sedative, diuretic, demulcent, and expectorant purpose ethnopharmacologically. Objective of the present study was investigation of anthelmintic activity of different extracts of Trichosanthes dioica seeds. Annelids, Pheretima posthuma and nematodes, Ascaridia galli were used to carry out experiments for anthelmintic activity. Piperazine citrate was used as a standard. Time required for paralysis and death (lethal time) of worms were noted for each sample of T. dioica extracts and standard. The results demonstrated that treatment with T. dioica seeds extract significantly (P<0.05-P<0.01) paralyzed and killed both of the worms, A. galli and earthworms. The activity was found to be increased with dose. Ethanol and ethyl acetate extracts activity at 60 mg/ml concentration were comparable to the well known anthelmintic agent Piperazine citrate (10 mg/ml). In conclusion, the use of the seeds of T. dioica as an anthelmintic has been confirmed and further studies are suggested to isolate the active principles responsible for the activity.